Neonatal immune response of Brazilian beef cattle to vaccination with Clostridium botulinum toxoids types C and D by indirect ELISA - Curci, V. C. M.; Nogueira, A. H. C.; Nobrega, F. L. C. [UNESP]; Araujo, R. F. [UNESP]; Perri, S. H. [UNESP]; Cardoso, T. C. [UNESP]; Dutra, Iveraldo dos Santos [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2010)
Types C and D strains of Clostridium botulinum are commonly related to avian and mammalian botulism. Although there are numerous vaccine recommendations, little research has been conducted to indicate the real effectiveness of vaccine timing or the ideal immunization protocol for young beef calves. Four commercially available vaccines, two bivalent (Clostridium botulinum types C and D; vaccines 1 and 2) and two polyvalent (all Clostridium spp. including Clostridium botulinum types C and D; vaccines 3 and 4), that are currently used in Brazilian herds, were tested in order to verify the maternal immune response. One hundred cows, divided into four vaccinated groups and one unvaccinated group, were given a two-dose subcutaneous immunization, at day zero, followed by a second dose given at 42 days post-vaccination, which corresponded to 40 days before birth. Serum samples (n = 75) were collected only from healthy neonatal calves at 0, 7, 45 and 90 days post-calving (DPC) and subjected to indirect ELISA using the purified C and D holotoxins as capture antigens. The serological profile showed that all vaccines were able to induce a satisfactory neonatal immune response to both holotoxins at 7 DPC. However, at 45 and 90 DPC, a significant reduction (p < 0.05) was observed in the antibody level against C and D holotoxins in all tested vaccines. Neonatal immunization in calves is compromised by significant levels of maternal antibodies so that the necessity of planning a calf vaccination program involves assessment of disease risks at the production site. Finally, our findings represent the first demonstration of maternal immunity transferred to neonatal beef calves, including immunity levels after vaccination against Clostridium botulinum toxoids C and D.
Keywords: Clostridium botulinum; neonatal immunity; cattle; botulism; Brazil